2012
DOI: 10.3310/hta16120
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical effectiveness and cost-effectiveness of Pharmalgen® for the treatment of bee and wasp venom allergy.

Abstract: An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per issue and for the rest of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 26 publications
(111 reference statements)
2
50
0
2
Order By: Relevance
“…4B). These data support the , and those treated with 2.5 mg/kg of BV reached 839±122 mm 3 . In addition, at day 15 after treatment, the 2.5 mg/kg BV-treated TC-1 tumor group showed that the tumor growth was significantly suppressed as compared with the 1.0 mg/kg BV-treated group (P<0.0001) and with the PBS group (P<0.0001).…”
Section: Protein Expression Of Hpv E6/e7 In Caski and Hela With Bv Trsupporting
confidence: 78%
See 2 more Smart Citations
“…4B). These data support the , and those treated with 2.5 mg/kg of BV reached 839±122 mm 3 . In addition, at day 15 after treatment, the 2.5 mg/kg BV-treated TC-1 tumor group showed that the tumor growth was significantly suppressed as compared with the 1.0 mg/kg BV-treated group (P<0.0001) and with the PBS group (P<0.0001).…”
Section: Protein Expression Of Hpv E6/e7 In Caski and Hela With Bv Trsupporting
confidence: 78%
“…TC-1 tumors were implanted in the abdomens of 4-to 5-week old female C57BL/6 mice by subcutaneous injection of 5x10 5 TC-1 cells in 100 µl of serum and antibiotic-free DMEM media (Gibco-BRL). When tumors reached a volume of 150-200 mm 3 , mice were randomly assigned to one of three groups to receive PBS, 1 mg/kg BV and 2 mg/kg BV (5 mice/group). The first day of treatment was designated as day 1.…”
Section: Reverse Transcription (Rt)-pcr and Real-time Pcr (Qrt-pcr) Amentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrarush protocols have been shown to be safe [9,12,[15][16][17]; however, other prospective studies have shown a rapid increase in dose to be an independent risk factor for adverse systemic reactions [13,18]. In the case of ultrarush protocols, this risk is increased 1.8-fold, although the protocols are costeffective [19,20]. We chose 3 protocols that had already been successfully tested by different groups in Spain [8,21] and are the approach used in most allergy departments in Spain.…”
Section: Discussionmentioning
confidence: 89%
“…[28]. Les revues systématiques et méta-analyses ont montré l'efficacité de l'immunothérapie par voie sous-cutanée dans l'allergie aux hyménoptères chez l'enfant et l'adulte (Grade A) [29][30][31]. La qualité de vie des patients recevant une immunothérapie est meilleure que celle des patients disposant d'un stylo d'adrénaline seul [32][33][34].…”
Section: Allergie Aux Venins D'hyménoptèresunclassified